PROJECT APPROACH TO THE ORGANIZATION OF EDUCATION ACTIVITIES AT THE UNIVERSITY - N. E. SERDITOVA; N. A. LUCHININA; L. S. Pavlova (Высшее образование в России)
The article highlights the main elements of the programme aimed at modernization of the educational activities of Tver State University. Today it faces a challenge to be a key figure in the development of Tver region. The implementation of the project approach and the system of mutually agreed projects and tasks will ensure a qualitatively new level of the entire education system of the upper Volga region. The authors dwell on the main projects in the education sphere implemented now by Tver State University.